2019
DOI: 10.14198/jhse.2020.153.03
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between isokinetic knee flexion and extension muscle strength, jump performance, dynamic balance and injury risk in female volleyball players

Abstract: The relationship between balance, knee muscle strength, jump height and risk of injury has not been clearly stated in female volleyball athletes. The study was to determine whether a correlation exists between knee joint isokinetic muscle strength, risk of injury, balance and jump height in female volleyball athletes. Twenty-two female volleyball athletes were involved into the study. Knee muscle strength were evaluated with the Biodex 3 ® isokinetic dynamometer. Jump performances were evaluated with the count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
2
19
0
6
Order By: Relevance
“…In addition, in the experimental group, the improvement of coordination abilities occurred in close connection with the improvement in the techniques implementation. The choice of these areas of sports training is consistent with the recommendations of other studies [36][37][38]. Modern researchers recommend using weights as a way of additional mobilization of analysers to improve special physical and technical readiness, increase coordination abilities.…”
Section: Pedagogysupporting
confidence: 69%
“…In addition, in the experimental group, the improvement of coordination abilities occurred in close connection with the improvement in the techniques implementation. The choice of these areas of sports training is consistent with the recommendations of other studies [36][37][38]. Modern researchers recommend using weights as a way of additional mobilization of analysers to improve special physical and technical readiness, increase coordination abilities.…”
Section: Pedagogysupporting
confidence: 69%
“…En el caso del voleibol, se han reportado efectos positivos por entrenamiento pliométrico en distintas semanas, tanto en la saltabilidad como en la fuerza explosiva (Berton, Lixandrão, Pinto e Silva, & Tricoli, 2018;Pereira et al, 2015;Sattler et al, 2018;Ziv & Lidor, 2010), en cuanto otro estudio realizo 6 semanas de entrenamiento pliométrico en agua en jugadores de voleibol femenino (15±1 años) reporto mejoras significativas en la saltabilidad (McKay et al, 2005), resaltando que el trabajo en el agua puede ayudar en la prevención de lesiones y adaptación de jóvenes jugadoras (McKay et al, 2005;Soylu, Altundað, Akarçeºme, & Yildirim, 2020).…”
Section: Post Entrenamientounclassified
“…There is a substantial body of evidence that quadriceps muscle strength supports the knee joint during various balance tasks. A recent study by Soylu et al (2020) also demonstrated a negative significant correlation between the overall stability index ( i.e., Biodex Balance System) with knee extension, and flexion peak torque of the dominant and non-dominant limb of angular velocity at 60° s −1 and 180° s −1 in female volleyball players. Soylu et al.…”
Section: Discussionmentioning
confidence: 76%
“…A recent study by Soylu et al (2020) also demonstrated a negative significant correlation between the overall stability index ( i.e., Biodex Balance System) with knee extension, and flexion peak torque of the dominant and non-dominant limb of angular velocity at 60° s −1 and 180° s −1 in female volleyball players. Soylu et al. ’s ( 2020 ) results reveal that the dynamic balance performance of the athletes increased as knee extension and flexion muscle strength increased.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation